Immunohistochemical analysis of CD34 to evaluate angiogenesis in chronic lymphocytic leukemia - Abdelateef, Shaymaa M.; Al-Rubaie, Haythem A.; Abid, Sabah A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Chronic lymphocytic leukemia (CLL) results from a progressive accumulation of long-lived, functionally incompetent, nonproliferating lymphocytes. Angiogenesis is defined as the formation of new capillaries from pre-existing blood vessels and plays an important role in the progression of solid tumors as well as several hematologic malignancies like CLL. Patients and methods: A retrospective cross-sectional study done on 68 patients with CLL compared with 15 control individuals (anemic patients), all recruited at the Medical City Teaching Laboratories from January 2005 to December 2008. The bone marrow biopsy (BMB) of each was re-examined histologically. Immunohistochemical (IHC) technique was performed on BMB sections utilizing monoclonal mouse CD34 class II antibody. Results: This study revealed higher microvessel density (MVD) in BM of CLL patients than normal control marrows. CLL patients had a mean MVD of 10.78 VS 4.26 miorovessel count/high power field (MVC/HPF) in control subjects. Significant inverse correlation was found between MVD and PCV levels and platelet count. A Significant positive correlation was found between MVD and the percentage of lymphocytes in the bone marrow, BM infiltration pattern and the modified Rai stage of CLL patients Conclusions: Angiogenesis in CLL BM was significantly higher than control marrows and was more accentuated with advanced clinical stage of the disease.